Social Commitment: voluntary, obligatory? A theological view on the freedom of a Christian - Andreas Prokopf (Ignatianum University Press, 2019)
In this article I would like to highlight our Erasmus+ K1 project  concerning the aspect of ´Voluntary Social Engagement´ in a German vocational school, work on the aspect of ´voluntary`, taking into account theological topics: ´Free Will´, the ´new man´ according St. Paul, the problem of `power and temptation` and finally draw consequences for project work in the field of social engagement from the perspective of theology. An empirical attempt is being taken to connect statements of Youngsters about their image of god and the consequences from this to the aims of social engagement. By the qualitative methodology of grounded theory categories emerge which can be crucial for concepts of social engagement.